GENETIC SOURCES AND MECHANISM OF MOLECULAR EVOLUTION OF THE A/HINI - 2009 INFLUENZA VIRUS CAUSING GLOBAL PANDEMIC IN HUMAN - Hoà, Lê Thanh (Vietnam Journal of Biotechnology, 2011)
Influenza A viras is well known as a special entity of undergoing multiple evolutionary process to gain its capability for genetic changes to form novel lineage(s)/subtype(s) either through mutation, ’antigen drift’ or reassortment, ’antigen shift’. Antigen shift is a process of exchanging genetic materials derived from reassortment of gene segments between virases, within and between subtypes, resulting in an antigenically novel viras that is capable of causing a worldwide pandemic. The novel A/HINI - 2009 (A/(HlNl)v; S-OIV) currently causing global pandemic is a-remarkable representative for such reassortment within and between lineages/subtype(s) of the influenza A viruses. A serial lineages and subtj^es of influenza A causing pandemics in the 20* century and the present HlNl (2009), are examples as consesquences ofthe evolutionary process of reassortment from many influenza A lineages/sublineages of human and animal origins. Among them, there have been encountered the lineages/subtypes: i) the HlNl which caused the Spanish flu pandemic in 1918; ii) the H2N2 which caused the Asian flu pandemic in 1957 - 1958; iii) the H3N2 which caused the Hongkong flu pandemic in 1968 - 1969; and iv) the novel HlNl reassortant which is causing the current 2009 pandemic. The A/HlNl - 2009 influenza lineage genetically, antigentically and pathogenically differs completely from the previous HlNl lineages; it is a human HlNl to be formed through a number of evolution stages from many genetic sources and lineages ofthe influenza viras. This is the resulting reassortant of either antigen drift and antigen shift (reassortment) from many swine, human and avian lineages of North American and Eurasian origins. The polymerase PB2 and PA were obtained from the H3N2 swine genetic source which previously reasserted from the North American avian and swine influenza; the PBl typically from the human A/H3N2; the hemagglutinin HA(Hl), nucleoprotein NP and non-stractural NS collected from the classical swine HlNl and H3N2; the NA(N1) and M obtained from the Eurasian H1N1/H3N2 Imeage of swine influenza. All the segments to constract the HlNl - 2009 have undergone multiple genetic variations compared to the previous genetic sources, particularly, hemagglutinin HA(Hl) differs about 28% in terms of nucleotide and amino acid of HAj and different glycosylation sites from the HA of H1N1(1918) and H1N1(2008). Likewise, the NA(N1) of A/HINI - 2009 has such high level of variation. Vietnam is currently one of nearly 150 nations confronting HlNl - 2009 pandemic and the infection wave spreads rapidly to many of cities/provinces. In this review, we are presenting informative data about the genetic sources and mechanism of molecular evolution to form the current human A/HINI - 2009, particularly, detailing its emergence history, circulation, general characteristics of evolution; mechanism of the viralence and genetic changing process; several features of measurement and prevention to be implemented. The emergence and circulation of the human A/HINI - 2009 in Vietnam poses the potential threat and high presure on us to confront a new influenza epidemiology in our country, in paralell with the H5N1 avian influenza circulating during many years now.